Electrode-integrated separator for lithium secondary battery and lithium secondary battery including same
The electrode integrated separation membrane for lithium secondary batteries, with its adhesive portion pattern and porous layer, addresses the adhesion and thermal stability issues of existing membranes, ensuring robust bonding and ionic conductivity.
Patent Information
- Application Number
- JP2024557796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-10-13
AI Technical Summary
Existing lithium secondary battery separation membranes suffer from inadequate adhesion to electrodes, leading to issues like partial lifting and wrinkling, and are prone to thermal instability and internal short circuits due to their material properties.
An electrode integrated separation membrane is developed, featuring an electrode portion with an electrode active material layer on a current collector, an adhesive portion pattern on the electrode active material layer, and a porous layer closely bonded through the adhesive pattern, containing a polymer binder and inorganic fine particles.
The solution achieves excellent bonding durability between the separation membrane and the electrode without hindering ionic conductivity, thereby enhancing the thermal stability and safety of lithium secondary batteries.
Smart Images

Figure 2025511643000001_ABST
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0141272 dated October 28, 2022 and Korean Patent Application No. 10-2023-0129785 dated September 26, 2023, and all contents disclosed in the documents of the Korean Patent Application are incorporated herein by reference.
[0002] The present invention relates to an electrode-integrated separator for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]
[0003] The demand for secondary batteries to be used as driving power sources for mobile phones, notebook computers, tablet computers, mobile batteries, electric vehicles, personal mobility devices, etc. is constantly increasing due to the increasing functionality of these devices. In particular, lithium secondary batteries, which have high operating voltages and high energy density per unit weight, are the most widely used.
[0004] A lithium secondary battery generally has a structure in which a chargeable and dischargeable electrode assembly having a positive electrode, a separator, and a negative electrode is mounted in a battery case. The positive electrode and the negative electrode are manufactured by applying a slurry containing an electrode active material to one or both sides of a metal current collector, followed by drying and rolling.
[0005] The separator is one of the important factors that determine the life of a secondary battery, and electrically insulates the positive and negative electrodes. The separator is required to have ion permeability and mechanical strength so that the electrolyte can pass through smoothly. As the range of applications of high-energy lithium secondary batteries expands, the demand for the safety of the separator at high temperatures is also increasing.
[0006] A commonly used separator, which is made of a separator substrate and an inorganic coating layer, does not have sufficient adhesion to the electrode due to the material properties of the membrane, which can lead to partial lifting or wrinkles at the interface between the electrode and the membrane. In addition, polyolefin, which is commonly used as a separator substrate, has thermal stability problems, such as melting at high temperatures.
[0007] To solve these problems, a method has been proposed in which the separator substrate is removed and the separator is formed only from an inorganic coating film. However, such separators still have insufficient adhesion to the electrodes and have extremely low insulation properties, making them vulnerable to internal short circuits when used in electrochemical devices. Furthermore, such separators have a fatal drawback in that they are easily broken due to their low tensile strength and elongation rate, which can cause micro-short circuits inside the electrode assembly. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides an electrode-integrated separator for a lithium secondary battery that has excellent bond durability between the separator and the electrodes without impairing ionic conductivity between the electrodes.
[0009] The present invention also provides a lithium secondary battery including the electrode-integrated separator. [Means for solving the problem]
[0010] According to one embodiment of the present invention, there is provided an electrode-integrated separator for a lithium secondary battery, comprising: an electrode part including an electrode active material layer laminated on an electrode current collector; an adhesive pattern formed on the electrode active material layer; and a porous layer that is closely bonded to the electrode active material layer via the adhesive pattern and includes a polymer binder and inorganic fine particles dispersed on the polymer binder.
[0011] According to another embodiment of the present invention, there is provided a lithium secondary battery including the electrode integrated separator.
[0012] Hereinafter, the electrode-integrated separator for a lithium secondary battery and the lithium secondary battery including the same according to the embodiment of the present invention will be described in more detail.
[0013] The terms and words used in this specification and the claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the invention, based on the principle that an inventor can appropriately define the concepts of terms in order to best describe his or her invention.
[0014] Unless otherwise defined herein, all technical and scientific terms have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. The terms used in the description of the present invention are merely for the purpose of effectively describing a particular embodiment, and are not intended to limit the present invention.
[0015] As used herein, the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates to the contrary.
[0016] As used herein, the meaning of "comprising" is to embody certain features, regions, integers, steps, operations, elements, components and / or components, and does not exclude the presence or inclusion of other certain features, regions, integers, steps, operations, elements, components and / or groups.
[0017] The present invention can be modified in various ways and can have various forms, and the specific embodiments are described in detail below. However, it is not intended to limit the present invention to the specific disclosed forms, but it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0018] In this specification, when the positional relationship of two parts is described using, for example, "on," "upper," "lower," "beside," etc., one or more other parts may be disposed between the two parts, unless the words "directly" or "indirectly" are used.
[0019] In this specification, when a temporal relationship is described using, for example, "after," "following," "next to," or "before," the terms "directly" or "immediately" are not used, and therefore non-consecutive cases may also be included.
[0020] As used herein, the term "at least one" should be understood to include all possible combinations of one or more of the associated items.
[0021] In the present invention, when any one layer is bonded to another layer "through" another layer, this means that the one layer and the other layer are laminated and bonded to each other through the other layer interposed in at least a portion of the area between the one layer and the other layer.
[0022] In the present invention, when any one layer is "closely bonded" to another layer via another layer, it means that the one layer and the other layer are laminated and bonded to each other via the other layer without any empty space between them.
[0023] According to one embodiment of the present invention, there is provided an electrode-integrated separator for a lithium secondary battery, comprising: an electrode part including an electrode active material layer laminated on an electrode current collector; an adhesive pattern formed on the electrode active material layer; and a porous layer that is closely bonded to the electrode active material layer via the adhesive pattern and includes a polymer binder and inorganic fine particles dispersed on the polymer binder.
[0024] As a result of the inventors' continued research, it was found that an electrode-integrated separator for a lithium secondary battery having the above-mentioned configuration can exhibit excellent bonding durability between the separator and the electrode without inhibiting ionic conductivity between the electrodes.
[0025] FIG. 1 is a cross-sectional view of an electrode-integrated separator for a lithium secondary battery according to one embodiment of the invention.
[0026] Referring to FIG. 1, an electrode integrated separator 100 for a lithium secondary battery according to an embodiment of the invention includes an electrode part 10 including an electrode active material layer 15 stacked on an electrode collector 13; an adhesive pattern 20 formed on the electrode active material layer 15; and a porous layer 30 closely bonded to the electrode active material layer 15 via the adhesive pattern 20.
[0027] In particular, the electrode integrated separator 100 for a lithium secondary battery has a structure in which the porous layer 30 is closely bonded to the electrode active material layer 15 of the electrode unit 10 via the adhesive pattern 20. As a result, the electrode integrated separator 100 can exhibit excellent thermal stability and ionic conductivity between the electrodes, while also exhibiting excellent bond durability between the porous layer 30 and the electrode unit 10.
[0028] According to one embodiment of the invention, the electrode portion 10 may be a negative electrode portion or a positive electrode portion.
[0029] The electrode part 10 can be obtained by a method of applying an electrode material containing a mixture of an electrode active material, a conductive material, and a binder onto an electrode current collector 13 and then drying the applied material to form the electrode active material layer 15.
[0030] The electrode current collector may be any material known in the art to which the present invention pertains that has conductivity without inducing a chemical change in the lithium secondary battery. For example, the electrode current collector may be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.
[0031] Preferably, the electrode current collector may have a thickness of 3 μm to 500 μm. The electrode current collector may have fine irregularities formed on its surface in order to increase adhesion to the electrode material. The electrode current collector may have various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc.
[0032] The conductive material can be used to impart electronic conductivity to the electrode.
[0033] The conductive material can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the lithium secondary battery. Non-limiting examples of the conductive material include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; or conductive polymers such as polyphenylene derivatives. The conductive material can be one or a mixture of two or more of the above examples.
[0034] The content of the conductive material may be adjusted within a range that does not cause a decrease in the capacity of the lithium secondary battery while exhibiting an appropriate level of conductivity, and may be 1 wt % to 10 wt % or 1 wt % to 5 wt % based on the total weight of the electrode material.
[0035] The binder is used to make the electrode material adhere well to the electrode current collector.
[0036] Non-limiting examples of the binder include polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon resin, etc. The binder may be one or a mixture of two or more of the above examples.
[0037] The content of the binder may be adjusted within a range that does not cause a decrease in the capacity of the lithium secondary battery while exhibiting an appropriate level of adhesiveness, and may be 1 wt % to 10 wt % or 1 wt % to 5 wt % based on the total weight of the electrode material.
[0038] When the electrode unit 10 is a positive electrode unit, the positive electrode active material can be any material capable of reversibly inserting and extracting lithium ions without any particular limitation.
[0039] For example, the positive electrode active material may be a composite oxide or phosphate containing lithium and a metal selected from cobalt, manganese, nickel, iron, or a combination thereof.
[0040] As another example, the positive electrode active material may be a compound represented by any one of the following chemical formulas: Li a A 1-b R b D2(0.90≦a≦1.8, 0≦b≦0.5);Li a E 1-b R b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);LiE 2-b R b O 4-c D c (0≦b≦0.5, 0≦c≦0.05);Li a Ni 1-b-c Co b R c D d (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, 0 <d≦2);Li a Ni 1-b-c Co b R c O 2-d Z d (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, 0 <d<2);Li a Ni 1-b-c Co b R c O 2-dZ2(0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni 1-b-c Mn b R c D d (0.90≦a≦1.8,0≦b≦0.5,0≦c≦0.05,0 <d≦2);Li a Ni 1-b-c Mn b R c O 2-d Z d (0.90≦a≦1.8,0≦b≦0.5,0≦c≦0.05,0 <d<2);Li a Ni 1-b-c Mn b R c O 2-d Z2(0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni b E c G d O2(0.90≦a≦1.8;0≦b≦0.9;0≦c≦0.5;0.001≦d≦0.1.);Li a Ni b Co. Co c Mn d G e O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0≦d≦0.5、0.001≦e≦0.1);Li a NiG b O2(0.90≦a≦1.8;0.001≦b≦0.1);Li a CoG b O2(0.90≦a≦1.8;0.001≦b≦0.1);Li a MnG b O2(0.90≦a≦1.8;0.001≦b≦0.1);Li a Mn2G b O4(0.90≦a≦1.8、0.001≦b≦0.1);QO2;QS2;LiQS2;V2O5;LiV2O5;LiTO2;LiNiVO4;Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Fe2(PO4)3(0≦f≦2);
[0041] In the above formula, A is Ni, Co, Mn, or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; Z is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; T is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.
[0042] The positive electrode active material may have a coating layer on its surface, or may be mixed with the positive electrode active material having a coating layer. The coating element contained in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof.
[0043] According to one embodiment, the positive electrode active material may be included in an amount of 80 wt% to 95 wt% based on the total weight of the electrode material. Preferably, the positive electrode active material may be included in an amount of 82 wt% to 95 wt%, 82 wt% to 93 wt%, 85 wt% to 93 wt%, or 85 wt% to 90 wt% based on the total weight of the electrode material.
[0044] When the electrode unit 10 is a negative electrode unit, the negative electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0045] Examples of the material capable of reversibly intercalating and deintercalating the lithium ions include carbonaceous materials such as crystalline carbon, amorphous carbon, or a mixture thereof. Specifically, the carbonaceous material may be natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitches, mesophase pitch based carbon fiber, carbon microbeads, petroleum or coal tar pitch derived cokes, soft carbon, and hard carbon.
[0046] The lithium metal alloy may be an alloy of lithium with a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.
[0047] The substances capable of being doped and undoped with lithium may be Si, Si-C composite, SiOx (0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Si is excluded), Sn, SnO2, Sn-R alloy (wherein R is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Sn is excluded), etc. And as the substances capable of being doped and undoped with lithium, at least one of the above examples and SiO2 can be mixed and used. The Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.
[0048] And the transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanate, etc.
[0049] Preferably, the negative electrode active material can contain one or more compounds selected from the group consisting of carbonaceous substances and silicon compounds. Here, the carbonaceous substance is one or more substances selected from the group consisting of natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon, which were exemplified above. And the silicon compound may be a compound containing Si exemplified above, that is, Si, Si-C composite, SiOx (0 < x < 2), the Si-Q alloy, a mixture thereof, or a mixture of at least one of these and SiO2.
[0050] According to one embodiment, the negative electrode active material may be included in an amount of 85 wt% to 98 wt% based on the total weight of the electrode material. Preferably, the content of the negative electrode active material may be 85 wt% to 97 wt%, alternatively 87 wt% to 97 wt%, alternatively 87 wt% to 95 wt%, or alternatively 90 wt% to 95 wt%, based on the total weight of the negative electrode material.
[0051] Meanwhile, the electrode integrated separator 100 for a lithium secondary battery includes an adhesive pattern 20 formed on the electrode active material layer 15 of the electrode unit 10 .
[0052] The adhesive pattern 20 is a pattern in which a plurality of adhesive units are arranged at predetermined intervals. The adhesive pattern 20 is formed on the electrode active material layer 15 to improve the bonding durability between the porous layer 30 and the electrode unit 10.
[0053] According to one embodiment, the adhesive pattern 20 may have a configuration including two or more adhesive units, or four or more adhesive units.
[0054] In order to improve the durability of the bond between the porous layer 30 and the electrode 10 through the introduction of the adhesive pattern 20, it is preferable that the adhesive pattern 20 includes two or more adhesive units, or four or more adhesive units. The upper limit of the number of the adhesive units included in the adhesive pattern is not particularly limited, since it can be appropriately adjusted depending on the ratio of the area of the electrode active material layer to the area occupied by the adhesive pattern.
[0055] According to one embodiment, the adhesive units may each independently have one or more cross-sectional shapes selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0056] 2-6 are each a cross-sectional view of a bond pattern according to an embodiment of the invention.
[0057] The adhesive pattern 20 according to FIG. 2 is composed of adhesive units 23 having a circular cross section. The adhesive pattern 20 according to FIG. 3 is composed of adhesive units 23 having a square cross section. The adhesive pattern 20 according to FIG. 4 is composed of adhesive units 23 having a rectangular cross section arranged in a stripe shape. The adhesive pattern 20 according to FIG. 5 is composed of adhesive units 23 having a circular cross section and adhesive units 25 having a cross section of a cross section. The adhesive pattern 20 according to FIG. 6 is composed of adhesive units 23 having a quadrant cross section, adhesive units 25 having a circular cross section, and adhesive units 27 having a semicircular cross section. FIGS. 2 to 6 show examples of a portion of the adhesive pattern, and the adhesive pattern can be expanded depending on the area of the electrode active material layer, and the number of the adhesive units can be increased.
[0058] According to one embodiment, in order to achieve uniform bonding durability through the introduction of the adhesive pattern, it is preferable that the adhesive patterns 20 are arranged at equal intervals between the centers of the adhesive units.
[0059] Here, the center of the adhesive unit may be determined based on its cross section. As an example, the center of a circular cross section is the center of the circle. As another example, the center of an elliptical cross section is the point where the major and minor axes of the ellipse intersect. As yet another example, the center of a sector-shaped cross section, such as a quadrant or semicircle, is the center of a circle inscribed in the cross section. As yet another example, the center of a polygonal or concave polygonal cross section is the center of a circle circumscribed in the cross section.
[0060] According to an embodiment, the adhesive pattern 20 may include adhesive units having two or more different cross-sectional shapes selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0061] Here, adhesive units having the same cross-sectional shape may be arranged at equal intervals around their centers. For example, adhesive units 23 having a circular cross-section in Fig. 5 are arranged at equal intervals around their centers. And, independently, adhesive units 25 having a cross-sectional shape in a cross-shape are arranged at equal intervals around their centers.
[0062] According to an embodiment, in the adhesive pattern 20, the adhesive units may be spaced apart such that the center-to-center distance between each adhesive pattern unit is 100 μm to 1500 μm.
[0063] Specifically, the spacing between the adhesive units may be 100 μm or more, alternatively 250 μm or more, alternatively 500 μm or more, and 1500 μm or less, alternatively 1200 μm or less, alternatively 1000 μm or less, based on the center-to-center distance between the adhesive pattern units.
[0064] Preferably, the adhesive units may be arranged at intervals such that the distance between the centres of each adhesive pattern unit is 100 μm to 1500 μm, alternatively 250 μm to 1500 μm, alternatively 250 μm to 1200 μm, alternatively 500 μm to 1200 μm, alternatively 500 μm to 1000 μm.
[0065] According to one embodiment, the cross-section of the adhesive unit may have a major axis diameter of 20 μm to 5000 μm.
[0066] Here, the major axis diameter can be determined based on the shape of the cross section of the adhesive unit as follows. As an example, the major axis diameter of a circular cross section means the diameter of the circle. As another example, the major axis diameter of an elliptical cross section means the major axis length of the ellipse. As another example, the major axis diameter of a sector-shaped cross section such as a quadrant or semicircle may mean the length of a line segment connecting two points where two radii and an arc meet. Alternatively, it may mean the radius of a quadrant or the diameter of a semicircle. As another example, the major axis diameter of a polygonal or concave polygonal cross section means the diameter of a circle circumscribing the cross section.
[0067] Specifically, the cross-section of the bond unit may have a major axis diameter of 20 μm or more, alternatively 100 μm or more, alternatively 200 μm or more; and 5000 μm or less, alternatively 4000 μm or less, alternatively 3000 μm or less.
[0068] Preferably, the cross-section of the adhesive unit may have a major axis diameter of 20 μm to 5000 μm, alternatively 100 μm to 5000 μm, alternatively 100 μm to 4000 μm, alternatively 200 μm to 4000 μm, alternatively 200 μm to 3000 μm.
[0069] According to one embodiment, in the bond pattern 20, the center-to-center distance and the major axis diameter of the cross section of the bond units may be determined within the aforementioned ranges depending on the proportion of the area occupied by the bond pattern.
[0070] According to an embodiment, the adhesive pattern 20 is preferably formed with an area ratio of 15% to 50% of the total area of the electrode active material layer 15 .
[0071] Specifically, the ratio of the area occupied by the adhesive pattern 20 to the total area of the electrode active material layer 15 may be 15% or more, or 16% or more, or 17% or more; and 50% or less, or 49% or less, or 48% or less.
[0072] In order to realize an effect of improving the durability of the bond between the porous layer 30 and the electrode part 10 through the introduction of the adhesive pattern 20, it is preferable that the ratio of the area occupied by the adhesive pattern 20 to the total area of the electrode active material layer is 15% or more, or 16% or more, or 17% or more.
[0073] The higher the ratio of the area occupied by the adhesive pattern 20, the better the bond durability can be achieved, but the lowering of the ion conductivity between the electrodes may result in a decrease in the capacity of the lithium secondary battery. Therefore, the ratio of the area occupied by the adhesive pattern to the total area of the electrode active material layer is preferably 50% or less, 49% or less, or 48% or less.
[0074] Preferably, the adhesive pattern 20 may be formed with an area ratio of 15% to 50%, alternatively 16% to 50%, alternatively 16% to 49%, alternatively 17% to 49%, or alternatively 17% to 48% of the total area of the electrode active material layer 15.
[0075] For example, referring to FIG. 7 and FIG. 8, the area ratio of the adhesive pattern 20 is U ) the area occupied by the adhesive pattern (A P ) can be calculated as a percentage.
[0076] According to one embodiment, the material of the adhesive pattern is preferably electrochemically stable and has adhesive properties suitable for bonding the electrode active material layer 15 and the porous layer 30 .
[0077] As an example, the binder used in forming the positive electrode active material layer and the negative electrode active material layer may be used as the adhesive portion.
[0078] Preferably, the adhesive portion may be one or more selected from the group consisting of polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon resin.
[0079] The adhesive may be the polymer binder used in forming the porous layer.As an example, the adhesive pattern may include one or more compounds selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
[0080] According to an embodiment, the thickness of the adhesive pattern 20 is preferably adjusted in the range of 0.1 μm to 10 μm, alternatively 0.1 μm to 5 μm, alternatively 0.5 μm to 5 μm, or alternatively 0.5 μm to 2 μm in order to exhibit suitable performance.
[0081] The adhesive pattern 20 may be formed on the electrode active material layer 15 by coating, dispensing, transfer, deposition, printing, spraying, etc. For example, the adhesive pattern 20 may be formed by gravure printing, micro gravure printing, offset printing, etc.
[0082] Meanwhile, the electrode integrated separator 100 for a lithium secondary battery includes a porous layer 30 closely coupled to the electrode active material layer 30 via the adhesive pattern 20 .
[0083] 1, the porous layer 30 is laminated and bonded without leaving any space between the porous layer 30 and the electrode active material layer 30 via the adhesive pattern 20. As a result, the electrode integrated separator 100 can exhibit excellent bond durability between the porous layer 30 and the electrode unit 10 without inhibiting ion conductivity between a counter electrode (not shown) laminated on the porous layer 30 and the electrode unit 10.
[0084] According to one embodiment, the porous layer 30 comprises a polymeric binder and inorganic fine particles dispersed on the polymeric binder.
[0085] The polymer binder may be gelled when impregnated with a liquid electrolyte, and may exhibit a high degree of swelling. The electrolyte injected after assembling the lithium secondary battery permeates the polymer binder, and the polymer binder that holds the absorbed electrolyte has electrolyte ion conduction ability. Therefore, the polymer binder has a solubility index of 15 to 45 MPa. 1 / 2 A polymer in which the following formula is given can be preferably used.
[0086] As an example, the polymer binder may be one or more compounds selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
[0087] The inorganic fine particles form micropores due to spaces between the particles, maintain their physical shape at high temperatures, and are electrochemically stable.
[0088] It is preferable that the inorganic fine particles do not undergo oxidation and / or reduction reactions in the operating voltage range of the secondary battery (e.g., 0 to 5 V based on Li / Li+). It is preferable that the inorganic fine particles have high electrolyte ion transfer ability. It is preferable that the inorganic fine particles have as low a density as possible so that they can be well dispersed in the polymer binder. And it is preferable that the inorganic fine particles have a high dielectric constant so that they can contribute to increasing the degree of dissociation of the electrolyte salt in the electrolyte.
[0089] Preferably, the inorganic fine particles may be one or more types selected from the group consisting of inorganic particles having a dielectric constant of 1 or more, inorganic particles having piezoelectricity, and inorganic particles having lithium ion transport ability.
[0090] As an example, inorganic particles such as SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, and SiC have a dielectric constant of 1 or more and can be preferably used as the inorganic fine particles.
[0091] As another example, the inorganic particles having piezoelectricity are non-conductors at normal pressure, but when a certain pressure is applied, they become conductive due to a change in their internal structure. The piezoelectric inorganic particles have a high dielectric constant characteristic of 100 or more. In addition, when a certain pressure is applied to the piezoelectric inorganic particles to stretch or compress them, charges are generated and one side is charged positively (+) and the other side is charged negatively (-), generating a potential difference between the two sides. Due to the characteristics of the piezoelectric inorganic particles, when an internal short circuit occurs at the electrodes of the secondary battery due to an external impact, it is possible to prevent the positive electrode and the negative electrode from coming into direct contact, thereby enabling a gradual decrease in voltage and improved safety. Examples of the piezoelectric inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), Pb(Mg 1 / 3 Nb 2 / 3 Inorganic particles such as PMN-PT, PbTiO3, and HfO2 can be preferably applied.
[0092] As another example, the inorganic particles having lithium ion transfer ability refer to inorganic particles that contain lithium elements and have the function of transferring lithium ions without storing lithium. The inorganic particles having lithium ion transfer ability can improve the conductivity of lithium ions in a battery. Examples of such inorganic particles include Li3PO4, Li x Ti y (PO4)3(0 <x<2、0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2、0<y<1、0<z<3)、(LiAlTiP) x O y(0 < x < 4, 0 < y < 13), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z Inorganic particles such as (0 < x < 3, 0 < y < 3, 0 < z < 7) are given as examples.
[0093] Preferably, the inorganic fine particles are SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, SiC, BaTiO3, Pb(Zr, Ti)O3, Pb 1-x La x Zr 1-y Ti y O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3, HfO2, Li3PO4, Li x Ti y (PO4)3(0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3(0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z(0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z It may be one or more selected from the group consisting of (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0094] Preferably, the inorganic fine particles have a particle size of 0.001 μm to 10 μm. In order to ensure dispersibility in the porous layer, it is preferable that the inorganic fine particles have a particle size of 0.001 μm or more. However, when the particle size of the inorganic fine particles is excessively large, the thickness of the porous layer increases and the mechanical properties deteriorate, and internal short circuits may occur during charge and discharge of the secondary battery due to an excessively large pore size. Therefore, it is preferable that the inorganic fine particles have a particle size of 10 μm or less.
[0095] According to one embodiment, the porous layer 30 can contain 10 to 99% by weight of the inorganic fine particles and 1 to 90% by weight of the polymer binder. In order to impart appropriate porosity and insulation to the porous layer, it is preferable that the inorganic fine particles are contained in an amount of 10% by weight or more. However, when the inorganic fine particles are contained in an excessive amount, the mechanical properties of the porous layer may deteriorate due to weakening of the adhesive force. Therefore, it is preferable that the inorganic fine particles are contained in an amount of 99% by weight or less.
[0096] According to one embodiment, the porous layer 30 preferably has a porosity within an appropriate range for the manifestation of the characteristics of the porous layer. When the porosity of the porous layer is excessively large, internal short circuits may occur during charge and discharge of the lithium secondary battery. Therefore, the porosity of the porous layer 30 is preferably 60% or less.
[0097] According to one embodiment, the thickness of the porous layer 30 is preferably adjusted in the range of 5 μm to 100 μm, or 5 μm to 50 μm, or 10 μm to 50 μm for the manifestation of appropriate performance.
[0098] According to one embodiment, the electrode active material layer 15 and the porous layer 30 can be bonded to each other by a conventional lamination method using the adhesive pattern 20. For example, the adhesive pattern 20 can be formed on the electrode active material layer 15 of the negative electrode part 10, and then the porous layer 30 can be laminated thereon under pressure.
[0099] According to another embodiment of the present invention, there is provided a lithium secondary battery including the above-described electrode-integrated separator 100.
[0100] For example, the lithium secondary battery may include an electrode assembly including a counter electrode disposed on a porous layer of the electrode-integrated separator; an electrolyte impregnated in the electrode assembly; and a battery case that hermetically houses the electrode assembly and the electrolyte.
[0101] The lithium secondary battery includes the electrode assembly described above, and thus exhibits excellent durability and stable performance.
[0102] The lithium secondary battery may have various shapes, such as a square shape, a cylindrical shape, and a pouch shape.
[0103] The lithium secondary battery can be used as an energy supply source with improved performance and safety in the fields of portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras; and in the fields of transportation means such as electric cars, electric bikes, and personal mobility devices.
[0104] According to an embodiment, the electrolyte may be any electrolyte known in the art to which the present invention pertains that is applicable to lithium secondary batteries, without any particular limitation. For example, the electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.
[0105] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0106] The non-aqueous organic solvent may be any solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery.
[0107] Specifically, the non-aqueous organic solvent may be an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether-based solvent such as dibutyl ether and tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (propylene carbonate). The solvent may be a carbonate solvent such as polycarbonate (PC); an alcohol solvent such as ethyl alcohol and isopropyl alcohol; a nitrile such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; and sulfolane.
[0108] Among the above examples, carbonate-based solvents are preferably used as the non-aqueous organic solvent.
[0109] In particular, in consideration of the charge / discharge performance of the battery and the compatibility with the sacrificial positive electrode material, a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate, propylene carbonate) and a linear carbonate having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate) can be preferably used as the non-aqueous organic solvent. In this case, it may be advantageous to use a mixture of the cyclic carbonate and the linear carbonate in a volume ratio of 1:1 to 1:9 for the expression of the above-mentioned performance.
[0110] As the non-aqueous organic solvent, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1-3:1 to 9:1 can be preferably used.
[0111] The lithium salt contained in the electrolyte is dissolved in the non-aqueous organic solvent and acts as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to promote the movement of lithium ions between the positive electrode and the negative electrode.
[0112] Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiFSI, LiTFSI, LiCl, LiI, LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, LiTFSI, and mixtures thereof.
[0113] The lithium salt may be contained in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt contained in this concentration range provides the electrolyte with appropriate conductivity and viscosity, thereby enabling the electrolyte to exhibit excellent electrolyte performance.
[0114] Optionally, the electrolyte may contain additives for the purposes of improving the life characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery.
[0115] For example, the additive may be a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivative, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The additive may be included in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte. Effect of the Invention
[0116] According to the present invention, there is provided an electrode-integrated separator having excellent bonding durability between the separator and the electrodes without inhibiting ionic conductivity between the electrodes, and a lithium secondary battery including the same. [Brief description of the drawings]
[0117] [Figure 1] 1 is a cross-sectional view of an electrode-integrated separator for a lithium secondary battery according to an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Diagram 3] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 4] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Diagram 5] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 6] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 7] 11A-11C are cross-sectional views illustrating a method for calculating the area percentage of a bond pattern according to an embodiment of the invention. [Figure 8] 11A-11C are cross-sectional views illustrating a method for calculating the area percentage of a bond pattern according to an embodiment of the invention. [Figure 9] 1 is a scanning electron microscope (SEM) image of a surface of a negative electrode part on which an adhesive pattern is formed according to an embodiment of the present invention. [Figure 10] 1 is a scanning electron microscope (SEM) image of a surface of a negative electrode part on which an adhesive pattern is formed according to an embodiment of the present invention. [Figure 11] 1 is a scanning electron microscope (SEM) image of a surface of a negative electrode part on which an adhesive pattern is formed according to an embodiment of the present invention. [Figure 12] 1 is a scanning electron microscope (SEM) image of a surface of a negative electrode part on which an adhesive pattern is formed according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0118] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these are presented as examples to help understand the invention. The following examples are not intended to limit the scope of the invention in any way, and it should be obvious to those skilled in the art that various changes and modifications are possible within the scope and technical concept of the present invention. EXAMPLES
[0119] Example 1 An aqueous active material slurry was prepared, which consisted of 95.6 wt% of an active material consisting of 90 wt% of graphite active material, which was a mixture of artificial graphite and natural graphite in a ratio of 3:7, 10 wt% of SiO, 1 wt% of acetylene black as a conductive material, and 1.1 wt% of carboxymethyl cellulose (CMC) and 2.3 wt% of styrene butadiene rubber (SBR) as binders. The active material slurry was applied to one side of a copper current collector with a thickness of 8 μm using a comma coater and dried. The resultant was rolled to form a negative active material layer (thickness 44 μm) with a porosity of 24%.
[0120] Using gravure printing equipment, an adhesive (polyvinylidene fluoride) was patterned on the negative active material layer in the form shown in Fig. 7. At this time, the adhesive unit having a circular cross section was formed to a thickness of 1 µm such that the cross section diameter was 400 µm, the center-to-center distance of the adhesive unit was 900 µm, and the area ratio of the adhesive pattern to the total area of the negative active material layer was 18%.
[0121] To prepare the porous layer composition, inorganic fine particles AlO(OH) and a dispersant (BYK, DISPERBYK-111) were mixed in N-methyl-2-pyrrolidone (NMP) to prepare an inorganic fine particle dispersion with a solid content of 42%. The particle size (D60) of the inorganic fine particles was analyzed to be 400 nm using a particle size analyzer. A binder solution was prepared by dissolving 6 wt% of poly(vinylidene fluoride-co-hexafluoropropylene) and 5 wt% of a dispersant (BYK, DISPERBYK-111) in NMP. A homogenizer mixer was used to obtain a slurry in which the inorganic fine particle dispersion and the binder solution were uniformly mixed. The slurry was applied onto the negative active material layer on which the adhesive pattern was formed, and then pressure lamination and drying were performed at 130° C. to obtain a negative plate having a porous layer with a thickness of 17 μm and a porosity of 50%, as shown in Figure 1. The composition of the porous layer was 90 parts by weight of the inorganic fine particles and 10 parts by weight of the polymer binder.
[0122] The negative electrode plate was punched out to a size of 31×43 cm using a die punching machine to prepare a negative electrode integrated separator.
[0123] A mixture of 94 wt% LiNiCoMnO2 (Ni:Co:Mn=8:1:1) as a positive active material, 3 wt% conductive carbon black (Super P;IMERYS Graphite & Carbon) as a conductive material, and 3 wt% polyvinylidene fluoride as a binder was uniformly dispersed in NMP to prepare a slurry. The slurry was applied to one side of an aluminum current collector, which was then dried and rolled to prepare a positive plate with a layer of positive active material. The positive plate was punched out to a size of 30 x 42 cm using a die punching machine to prepare a positive electrode part.
[0124] The positive electrode active material layer of the positive electrode part was placed on the porous layer of the negative electrode integrated separator, and then pressure lamination was performed at 90° C. to prepare an electrode assembly.
[0125] The electrode assembly was housed in a pouch to form a small cell, and an electrolyte was injected into the pouch to fabricate five lithium secondary batteries.
[0126] The electrolyte used was a non-aqueous organic solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, in which 1.0 M LiPF6 and 2 wt % vinylene carbonate (VC) were dissolved.
[0127] Example 2 An electrode-integrated separator and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that when forming the adhesive pattern, the adhesive units having a circular cross section were changed to have a cross-sectional diameter of 400 μm, a center-to-center distance of 730 μm, and an area ratio of the adhesive pattern to the total area of the negative electrode active material layer of 27%.
[0128] Example 3 An electrode-integrated separator and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that when forming the adhesive pattern, the adhesive units having a circular cross section were changed to have a cross-sectional diameter of 400 μm, a center-to-center distance of 630 μm, and an area ratio of the adhesive pattern to the total area of the negative electrode active material layer of 37%.
[0129] Example 4 An electrode-integrated separator and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that when forming the adhesive pattern, the adhesive units having a circular cross section were changed to have a cross-sectional diameter of 400 μm, a center-to-center distance of 550 μm, and an area ratio of the adhesive pattern to the total area of the negative electrode active material layer of 48%.
[0130] Comparative Example 1 An electrode integrated separator and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that the adhesive pattern was not formed and the porous layer was directly formed on the negative active material layer.
[0131] Comparative Example 2 An electrode integrated separator and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that the adhesive was formed by coating the adhesive on the entire surface of one side of the negative active material layer.
[0132] Experimental Example 1 The surface of the negative electrode part on which the adhesive patterns according to Examples 1 to 4 were formed was observed using a scanning electron microscope, and the images are shown in Figure 9 (Example 1), Figure 10 (Example 2), Figure 11 (Example 3), and Figure 12 (Example 4).
[0133] Experimental Example 2 The negative electrode integrated separators obtained in the examples and comparative examples were subjected to a 180 degree peel strength test according to the test method of ASTM D3330 (2018) using a TA-XT2 plus device manufactured by Stable Micro Systems.
[0134] After the sample (negative electrode integrated separator) was fixed vertically to the ground, tape (3M Scotch Tape, 18 mm wide) was attached in a U-shape on the porous layer. One end of the tape was placed on the grip of the device and pulled vertically to the ground (measurement speed 300 mm / min, measurement distance 5 cm) to measure the strength of the force applied to the grip when peeling off at 180 degrees. The test was performed on five samples each, and the average 180 degree peel-off force is shown in Table 1 below.
[0135] [Table 1]
[0136] In the 180 degree peel strength test, it was confirmed that the porous layer of the negative electrode integrated separator of the Example did not peel off and the tape peeled off easily. In contrast, it was confirmed that the porous layer of the negative electrode integrated separator of Comparative Example 1 peeled off from the negative electrode part, causing irregular stick-slip behavior.
[0137] Experimental Example 3 The lithium secondary batteries obtained in the above Examples and Comparative Examples (five samples each) were subjected to a CC-CV mode at 25° C. at 0.1 C (reference capacity 4.5 mAh / cm 2 ) to 4.2 V, and the voltage was maintained in CV mode until it reached 0.05 C. Then, the formation process was performed by discharging to 2.5 V at 0.1 C, and the discharge capacity (mAh) and ionic conductivity (mS / cm) were averaged for five samples and shown in Table 2.
[0138] During the formation process, the number of defective samples that were not properly charged or discharged due to short circuits or the like was counted out of five samples each manufactured in the example and comparative example. The results are shown in Table 2.
[0139] [Table 2]
[0140] Referring to Table 2, the lithium secondary batteries of the examples exhibited high discharge capacity and excellent assembly stability without defects due to short circuits between the negative and positive electrodes.
[0141] The lithium secondary battery of Comparative Example 1 exhibited a high level of discharge capacity, but had a high short-circuit rate of the electrodes due to the lack of an adhesive.
[0142] The lithium secondary battery of Comparative Example 2 showed the poorest levels of discharge capacity and ionic conductivity due to the adhesive being introduced into the entire negative active material layer.
[0143] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims set forth below. [Explanation of symbols]
[0144] 100: Electrode-integrated separator for lithium secondary batteries 10: Electrode part 13: Electrode current collector 15: Electrode active material layer 20: Bonding pattern 23, 25, 27: Adhesive unit 30: Porous layer A U :Unit area A P : The above A U The area occupied by the adhesive pattern
Claims
1. an electrode part including an electrode active material layer laminated on an electrode current collector; An adhesive pattern formed on the electrode active material layer; and a porous layer that is intimately bonded to the electrode active material layer through the adhesive pattern and includes a polymer binder and inorganic fine particles dispersed on the polymer binder; An electrode-integrated separator for a lithium secondary battery comprising:
2. 2. The electrode integrated separator for a lithium secondary battery according to claim 1, wherein the adhesive pattern is formed with an area ratio of 15% to 50% of the total area of the electrode active material layer.
3. The electrode-integrated separator for a lithium secondary battery according to claim 1 , wherein the adhesive pattern includes four or more adhesive units.
4. 4. The electrode-integrated separator for a lithium secondary battery according to claim 3, wherein the adhesive units each independently have at least one cross-sectional shape selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
5. The electrode-integrated separator for a lithium secondary battery according to claim 3 , wherein the adhesive units are arranged with the same intervals between the centers of the adhesive units.
6. The electrode-integrated separator for a lithium secondary battery according to claim 3, wherein the adhesive units are arranged at intervals such that the center-to-center distance between each adhesive pattern unit is 100 μm to 1500 μm.
7. 4. The electrode-integrated separator for a lithium secondary battery according to claim 3, wherein the cross section of the adhesive unit has a major axis diameter of 20 μm to 5000 μm.
8. 2. The electrode-integrated separator for a lithium secondary battery according to claim 1, wherein the adhesive pattern comprises at least one compound selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
9. 2. The electrode-integrated separator for a lithium secondary battery according to claim 1, wherein the porous layer comprises 10 to 99 wt % of the inorganic fine particles and 1 to 90 wt % of the polymer binder.
10. 2. The electrode-integrated separator for a lithium secondary battery according to claim 1, wherein the polymer binder is at least one compound selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
11. The inorganic fine particles are SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , boehmite (AlO(OH)), Al(OH) 3 , TiO 2 , SiC, BaTiO 3 , Pb(Zr,Ti)O 3 , Pb 1-x La x Zr 1-y Ti y O 3 , Pb(Mg 1/3 Nb 2/3 )O 3 - PbTiO 3 , HfO 2 , Li 3 PO 4 , Li x Ti y (PO 4 ) 3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO 3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x SiS z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z 2. The electrode-integrated separator for a lithium secondary battery according to claim 1, wherein x is at least one selected from the group consisting of: (0<x<3, 0<y<3, 0<z<7).
12. 2. The electrode-integrated separator for a lithium secondary battery according to claim 1, wherein the inorganic fine particles have a particle size of 0.001 μm to 10 μm.
13. A lithium secondary battery comprising the electrode-integrated separator according to claim 1.
Citation Information
Patent Citations
Lithium battery pole piece and preparation method and application thereof
CN113328063A
Separator for lithium battery, lithium battery including the same, and method of manufacturing lithium battery
JP2015099777A